Determinants of market production of cooking banana in Nigeria - Tshiunza, M.; Lemchi, J.; Tenkouano, A. (African Journals Online, 2001)
The factors that influence farmers' decisions to produce cooking banana for market in southeast Nigeria were examined. Data were collected from a random sample of 217 farmers through the use of a structured questionnaire. Results of the study indicate that about 80% of the farmers interviewed produce cooking banana both for household consumption and for sale. The proportion of cooking banana sold ranged from 10% to 90% with an average of 45%. Thus, cooking banana performs the dual role of providing food for the households, as well as being an additional source of cash income. Tobit regression analysis revealed that the price and the ripening stage at sale of cooking banana, as well as the presence of middlemen in the marketing chain were the most important determinants of the proportion of cooking banana planted for market. This indicates that cooking banana growers readily respond to market forces. Age and gender ownership of cooking banana also influenced the proportion of the crop planted for market. Increased involvement of wholesalers and processors in the marketing chain of the crop will probably enhance its market in the region.